2021
DOI: 10.1128/msystems.00646-21
|View full text |Cite
|
Sign up to set email alerts
|

IS 26 Is Responsible for the Evolution and Transmission of bla NDM -Harboring Plasmids in Escherichia coli of Poultry Origin in China

Abstract: Carbapenem resistance in members of the order Enterobacterales is a growing public health problem that is associated with high mortality in developing and industrialized countries. Moreover, in the field of veterinary medicine, the occurrence of New Delhi metallo-β-lactamase-producing Escherichia coli isolates in animals, especially food-producing animals, has become a growing concern in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 42 publications
0
24
1
Order By: Relevance
“…Plasmid pHNBYF33-1, which belonged to IncHI2-ST3, was 238 926 bp in length with a GC content of 46.30% and carried 12 resistance genes. The BLASTn results indicated that plasmid pHNBYF33-1 exhibited high similarity (≥99.9% identity and ≥93.4% coverage) to four bla NDM-5 -carrying IncHI2 plasmids deposited in GenBank, i.e., pNDM33-1 (MN915011) ( Zhao et al, 2021b ), GFQ9D68 Contig5 (JAGFYC010000005), GDQ8D151 plasmid1 (JAGFYD010000002), and GDQ20D15 plasmid1 (JAGFYB010000003) ( Figure 1B ). Interestingly, all four plasmids were carried by E. coli strains recovered from ducks in Guangdong, China.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Plasmid pHNBYF33-1, which belonged to IncHI2-ST3, was 238 926 bp in length with a GC content of 46.30% and carried 12 resistance genes. The BLASTn results indicated that plasmid pHNBYF33-1 exhibited high similarity (≥99.9% identity and ≥93.4% coverage) to four bla NDM-5 -carrying IncHI2 plasmids deposited in GenBank, i.e., pNDM33-1 (MN915011) ( Zhao et al, 2021b ), GFQ9D68 Contig5 (JAGFYC010000005), GDQ8D151 plasmid1 (JAGFYD010000002), and GDQ20D15 plasmid1 (JAGFYB010000003) ( Figure 1B ). Interestingly, all four plasmids were carried by E. coli strains recovered from ducks in Guangdong, China.…”
Section: Resultsmentioning
confidence: 99%
“…In these four IncHI2-type plasmids, the bla NDM-5 gene was identically embedded in a novel composite transposon (IS 3000 -ΔIS Aba125 -IS 5 -ΔIS Aba125 - bla NDM-5 - ble MBL - trpF - tat -∆ dct -IS 26 -∆ umuD -∆IS Kox3 -IS 3000 ) inserted between IS 1 and IS 10R of the multidrug resistance region of the IncHI2 plasmid with 5 bp target site duplications (TSDs) (ACTTT). Previous research has found that excision of this transposon from the plasmid pNDM33-1 forms a circular intermediate ( Zhao et al, 2021b ). Here, we renamed this novel 13 918 bp long transposon as Tn 7051 (https://transposon.lstmed.ac.uk/).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the evolution of pCLDRW_444k was closely related to IS 26 ( Table 1 and Fig. S1), which may facilitate the formation of various plasmid types and accelerate the evolution of MDR plasmids ( 25 ).…”
Section: Resultsmentioning
confidence: 99%